Information Disorder and Symbolic Violence in Social Media: A Narrative Literature Review of Indonesian Adolescents' Digital Communication - Irwanto, Irwanto; Bahfiarti, Tuti; Unde, Andi Alimuddin; Achmad Sulfikar (Palakka : Media and Islamic Communication, 2025)
The transformation of the digital communication landscape has presented the phenomenon of information disorder that has the potential to construct symbolic violence, especially among Indonesian adolescents as active users of social media. This research aims to analyze how digital communication patterns in the form of information disorder shape and perpetuate symbolic violence, as well as its impact on the communication behavior and social interaction of Indonesian adolescents. Through a narrative literature review approach, this research integrates findings from various academic sources, focusing on the dynamics of digital communication, manifestations of symbolic violence, and interaction patterns on social media. The analysis reveals that information disorder has created new communication patterns that can systematically trigger and perpetuate various forms of symbolic violence in the digital space. The complexity of interactions between digital communication patterns, sociocultural contexts, and the characteristics of social media platforms influences adolescents' vulnerability to this phenomenon. The identified impacts reveal significant changes in adolescents' communication patterns and social interactions, including transformations in how they construct meaning, establish identity, and form social relations in digital spaces. The study also identified that effective communication strategies in impact mitigation should integrate digital literacy with Media and Information Literacy (MIL), supported by participatory communication and community empowerment approaches. The findings make a significant contribution to the development of a more effective communication model in protecting the digital well-being of Indonesian youth.